Study on emission factor and reduction potential of organic solid waste gasification process - Deyong Peng; Xianan Xiang; Zhiya Deng; Xuehua Zhou; Bo Wang; Chunhui He (Case Studies in Thermal Engineering, 2024)
This paper conducts an in-depth study on the gasification treatment of Organic Solid Waste (OSW) and its carbon emissions, intending to fill the gap in the existing literature regarding the calculation methods for carbon emissions from OSW gasification. The study establishes a methodology for calculating carbon emission factors during the OSW gasification process and explores the potential for negative carbon emissions. For this purpose, indicator including the Carbon Dioxide Equivalent Warming Number (CEWN) is used to assess the greenhouse gas emissions of the gasification process by calculating carbon emission factors under different gasification conditions. It is found that within a certain range, increasing the gasification temperature, Equivalence Ratio (ER), and Steam to Biomass ratio (S/B) can positively influences the achievement of negative carbon emissions. These findings hold significant implications for optimizing the OSW gasification process, reducing carbon emissions, and ultimately achieving carbon neutrality. Furthermore, this study fills a critical void in the gasification field within the IPCC framework and offers essential guidance for promoting to achieve peak carbon emissions in the gasification industry and accelerating the goal of carbon neutrality.